Delayed Autotransplantation of Permanent Impacted Maxillary Canine - Mohamed Hisham Mohamed Jali; Noor Hayati Abdul Razak (USIM Press, 2024)
MJoSHT 2021, Volume 7, Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience. eISSN: 2601-0003